The Efficacy of Ice Cubes in Patients with Heart Failure - Septa Meriana Lumbantoruan; Lisandra Maria Goretti Sidabutar (Malahayati Nursing Journal, 2023)
ABSTRACT Heart failure (HF) as abnormal heart structure and function increases neurohormonal response and sympathetic activity resulting in a renin-angiotensin-aldosterone system (RAAS). Congestion as the result of RAAS, increase signs and symptoms of HF including thirst. Fluid restriction as the recommendation to reduce congestion is increased thirst in patients with HF.  The purpose of this study is to evaluate the effectiveness of ice cubes on thirst intensity, thirst distress, hospitalization, and mortality in patients with HF. This research implied quasi-experimental research, with one group pre and post-design. The sample recruited was 13 samples from outpatients and inpatients of a general hospital in Jakarta. Diagnosis must be HF by the cardiologist, over 18 years old, and in stable condition. Thirst intensity was measured by a visual analog score of 0-100, thirst distress was measured by thirst distress scale-heart failure, hospitalization, and mortality were measured by asking the patients or the family. There is a significant difference in thirst intensity before and after intervention (p 0.05); and there is also a significant difference in thirst distress before and after intervention (p 0.05). However, no difference in hospitalization and mortality after the ice cubes intervention. It is important for healthcare professionals or families to apply ice cubes sucking in patients with HF. The inpatients' patients are the most important to use the ice cubes to reduce thirst intensity and thirst distress due to thirst is higher in hospitalized patients with HF. Keywords: Ice Cubes, Thirst, Heart Failure